DIVERSIDADE E PADRÕES DE DISTRIBUIÇÃO DE MAMÍFEROS DOS CAMPOS DO URUGUAI E SUL DO BRASIL - Queirolo, Diego (Boletín de la Sociedad Zoológica del Uruguay, 2017)
For the first time the mammalian fauna of the Pampas from Uruguay and southern Brazil was considered as a whole, despite political borders. The study area comprises the Uruguayan territory and the Pampa biome in Brazil. Information on species distribution in the study area was obtained from different sources and a geographical distribution map was elaborated for each species. Information was obtained from scientific collections and literature. In general, 3,480 registers were considered (1,800 from Uruguay and 1,680 from Brazil), totaling 1,231 different localities (712 in Uruguay and 519 in Brazil). One hundred fifthteen species were identified (73 from Uruguay and 110 from Rio Grande do Sul, Brazil), being five of them endemic species and seven almost distributed exclusively in the study area. The small mammals (rodents, bats and marsupials) conform 73% of the registered genera found and almost 77% of the total number of species. The localities, registers and species richnessare concentrated near research institutions and protected areas. A substitution between northern forestal species and southern open areas species are clear. This work intended to collaborate with essential information in order to elaborate conservation politics that consider the entire region, independent of the countries that compose it.